DETERMINANTS OF THE INTERNET GENERATION CUSTOMER LOYALTY IN INDONESIA TELECOMMUNICATION MOBILE SERVICES: DOES OF CUSTOMER SATISFACTION PLAY A MEDIATION ROLE? - Yacob, Syahmardi; Johannes; Edward (Universitas Brawijaya, Indonesia, 2022)
The study investigates the iGen customer loyalty model that is affected by service quality, culture, loyalty program, and trust through customer satisfaction. Following the conceptual model, an inclusive set of hypotheses have been developed. The needed data were collected from 663 samples using an online survey, and Structural Equation Model with Smart Partial Least Square was applied to test the model and hypotheses. The research found that service quality, culture, loyalty programs, and trust are combined to predict customer loyalty. Trust and loyalty programs exert a more powerful impact on customer loyalty than service quality and culture variables. Customer satisfaction is a mediator between service quality, loyalty programs, customer trust, and customer loyalty. The results have some critical academic and professional implications for determining the model of consumer loyalty and the uniqueness of internet generation (iGen) in mobile communication services. The study can be used as a role model in formulating a marketing strategy management with a competitive advantage in mobile communication services in Indonesia.